Melasma dan Penggunaan Kontrasepsi Oral Jangka Panjang: Suatu Studi Kohort Retrospektif Berbasis Komunitas - Susila, Ida; Ningsih, Eka Sarofah; Muthoharoh, Husnul; Ummah, Kholifatul (Poltekkes Kemenkes Bandung, 2026)
Background: Melasma is a common skin disorder often influenced by hormonal factors such as estrogen and progesterone. Combined oral contraceptives (COCs), which contain both hormones, are widely used in Indonesia and may contribute to melasma, especially among long-term users. Objective: This study aimed to examine the association between prolonged COC use and melasma among women in Lamongan Regency, Indonesia. Methods: Using a retrospective cohort design, 20 reproductive-aged women were selected through purposive sampling. Data were collected via structured interviews and clinical observation, and analyzed using the Chi-square test. Results: Results showed that 55% of participants developed melasma, with a significant association between COC use duration and melasma occurrence (p = 0.024). Women who used combined oral contraceptives for ≥3 years showed a trend toward higher odds of developing melasma compared to those who used COCs for <3 years (OR = 8.0; p= 0.024. Conclusion: These findings underscore the need for integrating dermatological considerations into contraceptive counseling, particularly in primary healthcare facilities.